Big bubble deep anterior lamellar keratoplasty: the collagen layer in the wall of the big bubble is unique. (30th March 2015) - Dua, Harminder S.; Mastropasqua, Leonardo; Faraj, Lana; Nubile, Mario; Elalfy, Mohamed S.; Lanzini, Manuela; Calienno, Roberta; Said, Dalia G.
Abstract Purpose In big bubble (BB), deep anterior lamellar keratoplasty intracorneal injection of air separates Descemet's membrane (DM) and the pre‐Descemet's layer (Dua's layer [DL]) to create a type 1 BB. We tested the hypothesis that air injection after excision or ablation of DL will fail to produce a BB. Methods Nine human sclero‐corneal discs were used. Three served as controls. In three, a type 1 BB was created, the bubble wall was excised and more air injected in an attempt to create another BB. In three samples, the DM was removed and 22μ of posterior cornea were ablated by phototherapeutic keratectomy (PTK). Air was injected to induce formation of a BB. Tissue from these experiments was subjected to light and electron microscopy. Results In all three control eyes, a type 1 BB (DL + DM) was obtained. Air injection after excision of the type 1 BB wall in three samples failed to produce another BB. Following PTK of DL, injection of air failed to create a BB in all three samples. Multiple points of air leak from the deep stroma were observed in all six samples. Light and electron microscopy showed a clear distinction between the ablated and non‐ablated areas of cornea. Conclusions This study supports the hypothesis that a BB cannot be created once the DL is excised or ablated. This adds to evidence that DL is unique. It also demonstrates that DL is not a random separation of deep stroma of the cornea.